Mitochondrial Dysfunction, Oxidative Stress and Neuroinflammation in Neurodegeneration with Brain Iron Accumulation (NBIA) - Isabel Hinarejos; Candela Machuca; Paula Sancho; Carmen Espinós (Antioxidants, 2020)
The syndromes of neurodegeneration with brain iron accumulation (NBIA) encompass a group of invalidating and progressive rare diseases that share the abnormal accumulation of iron in the basal ganglia. The onset of NBIA disorders ranges from infancy to adulthood. Main clinical signs are related to extrapyramidal features (dystonia, parkinsonism and choreoathetosis), and neuropsychiatric abnormalities. Ten NBIA forms are widely accepted to be caused by mutations in the genes PANK2, PLA2G6, WDR45, C19ORF12, FA2H, ATP13A2, COASY, FTL1, CP, and DCAF17. Nonetheless, many patients remain without a conclusive genetic diagnosis, which shows that there must be additional as yet undiscovered NBIA genes. In line with this, isolated cases of known monogenic disorders, and also, new genetic diseases, which present with abnormal brain iron phenotypes compatible with NBIA, have been described. Several pathways are involved in NBIA syndromes: iron and lipid metabolism, mitochondrial dynamics, and autophagy. However, many neurodegenerative conditions share features such as mitochondrial dysfunction and oxidative stress, given the bioenergetics requirements of neurons. This review aims to describe the existing link between the classical ten NBIA forms by examining their connection with mitochondrial impairment as well as oxidative stress and neuroinflammation.